Autoimmune encephalitis with mGluR5 antibodies: A case series from China and review of the literature - Guo, Kundian; Liu, Xu; Gong, Xue; Li, Aiqing; Liu, Yue; Li, Xingjie; Zhou, Dong; Hong, Zhen (Frontiers in Immunology, 2023)
Background Only 15 patients of autoimmune encephalitis with metabotropic glutamate receptor 5 (mGluR5) antibodies have been reported worldwide since 2011, mostly from western countries. Patients with different genetic backgrounds are necessary to further clarify the clinical phenotype and prognosis of this rare disease. Objective We initially describe a case series from China to confirm the previous findings, expand the clinical phenotype, and identify the prognostic factors of autoimmune encephalitis with mGluR5 antibodies. Methods Observational data with follow-up were prospectively collected from autoimmune encephalitis patients with mGluR5 antibodies. Clinical information and outcomes on current and previously reported cases were combined and analyzed. Results We identified five patients (median age 35 years); two were female. The main clinical manifestations were behavioral/personality changes (five of five, 100%) and cognitive disorders (four of five, 80%), accompanied with other neurologic symptoms. Hypoventilation occurred in two (40%) patients and could be fatal. One patient had meningoencephalitis, suggesting a new phenotype in anti-mGluR5 encephalitis. We first reported teratoma in a paraneoplastic case. All patients received immunotherapy. At the last follow-up (median 18 months), two (40%) patients showed complete recovery, two (40%) patients showed partial recovery, and one (20%) patient died. One (20%) patient had multiple relapses. Together with the 15 previously reported cases, associated tumors occurred in seven of 12 (58%) Western patients vs. one of eight (13%) Chinese patients. Modified Rankin Scale (mRS) scores at the last follow-up (median 31 months) were available in 16 patients. Patients with bad outcomes (mRS > 2, n = 4) were more likely to have hypoventilation at onset and higher mRS scores at peak of the disease. Conclusions The clinical phenotype of anti-mGluR5 encephalitis is variable. Fewer paraneoplastic cases were observed in Chinese patients. Most patients showed good response to immunotherapy and cancer treatment. The clinical outcomes were favorable in most patients.